PENGARUH PENJADAPAN TERHADAP KADAR SARI KAJU TUSAM (Pinus merkusii Jungh. et de Vriese) - Soeprapti S.I Kaseno; Sri Margono (JURNAL SELULOSA, 1965)
The effect of tapping Pinus merkusii upon its extractive matters was studied.The extracttve matters were separated from the wood samples using a one to twomixture of alcohol and benzene in a Soxhlet apparatus.Three Pinus merkusii trees were studied, the first tree had been tapped for 3 months and was still being tapped when felled. The second tree had been tapped for 6 months and had afterwaids been left for 1/2 year before felling. The third tree has not been tapped.The effect of tapping was studied up to a height of 10 meters.The study reveals the following: wounding the tree stimulate the resin - yielding cell of the wood. Thus the formation of the extraneous materials in the tree increase.Samples taken from the tree which had been tapped and then left for 1/2 year before feling, showed a high extractive content, especially at regions near the face of the wound. It can be seen even with the naked eye, that this parts was heavily impregnated with resineous matters. The effect of the tapping upon the upper parts the tree above the wound was negligible.Samples taken from the tree which was still being tapped, showed a lower than average extractive content, for most of the resin was secreted as oleoresin.The presence of branching and knots within the trunk of the tree, showed a high extractive content in that part of the tree and a darker coloration of the wood.The infuence of tapping operation on other wood components was negligible.